(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Aortic arch surgery is the challenging and most difficult surgery among the cardiovascular operations. Cerebral and spinal complications are the most feared and common complications of aortic arch surgery. With best available techniques for cerebral and spinal protection, anesthetic management and good post-operative care; aortic arch surgery is considerably safer nowadays and satisfactory results can be achieved in most patients. Also, selecting the sites for arterial cannulation to maintain whole body circulation, during isolation of the aortic arch to operate on it, need proper anatomical description of the extent of the aneurysm. This is also achievable by the availability of the imaging techniques like Computed Tomography (CT) with or without contrast, CT Angiography (CTA) and Magnetic Resonance Imaging (MRI). We are reporting a case of aneurysm of aortic arch in a young adult, who had undergone repair under cardiopulmonary bypass and deep hypothermia with low flow and had normal convalescence without any cerebral or spinal complications.